Corrosion mechanism and damage characteristic of steel fiber concrete under the effect of stray current and salt solution. (3rd January 2022) - Xu, Wenqiang; Li, Yu; Li, Hanzhang; Wang, Kang; Zhang, Chengpeng; Jiang, Yibo; Qiang, Sheng
Highlights: Stray current and salt solution corrosion test for steel fiber reinforced concrete (SFRC). Non-destructive test for SFRC corrosion detection. Most destructive chloride ion and corrosion mechanism to SFRC. Quantitative relationship between the main influencing factors and damage degree. Comparative analysis of experimental results and numerical simulation. Abstract: Steel fiber reinforced concrete (SFRC) has been widely used in construction and transportation due to its superior mechanical properties. From the perspective of structure, SFRC is a potential solution to the problem of stray current induced corrosion in electrical railway systems. However, the corrosion mechanism of SFRC under the coupling effect of stray current and salt solution is not clear, and the change of mechanical properties in the process still lacks a quantitative description, so it is difficult to predict the structural life. In this paper, different corrosive media were selected for the stray current induced corrosion test of SFRC, in which the chloride concentration was adjusted to study its influence on the corrosion rate. Ultrasonic and electric current were combined to monitor the corrosion process. The colorimetric and titration method were used to measure the chloride depth and concentration in the specimen after corrosion, mercury intrusion porosimetry was employed to determine the pore structure. It is found that chloride is the most destructive to SFRC and dominates the corrosion process, while sulfate and caustic alkali contribute secondary effect. Chloride destroyed the passive film on the surface of the steel fiber and corroded it to form a local rust expansion area, causing concrete damage and reducing mechanical properties. In addition, if the damage degree reaches 0.3 ∼ 0.4, the structure will be destroyed. When the environmental chloride concentration reaches the threshold 0.6 mol/L, the higher the concentration, the faster the SFRC corrosion. The quantitative relationship between the main influencing factors (concentration of chloride, corrosion time and chloride penetration depth) and damage degree is proposed based on the experimental data. The research may provide reference for the application of SFRC in electric railway projects.